18‐month‐olds fail to use recent experience to infer the syntactic category of novel words. Issue 2 (4th September 2020) - Havron, Naomi; Babineau, Mireille; Christophe, Anne
Abstract: Infants are able to use the contexts in which familiar words appear to guide their inferences about the syntactic category of novel words (e.g. 'This is a' + 'dax' ‐> dax = object). The current study examined whether 18‐month‐old infants can rapidly adapt these expectations by tracking the distribution of syntactic structures in their input. In French, la petite can be followed by both nouns ( la petite balle, 'the little ball') and verbs ( la petite mange, 'the little one is eating'). Infants were habituated to a novel word, as well as to familiar nouns or verbs (depending on the experimental group), all appearing after la petite . The familiar words served to create an expectation that la petite would be followed by either nouns or verbs. If infants can utilize their knowledge of a few frequent words to adjust their expectations, then they could use this information to infer the syntactic category of a novel word – and be surprised when the novel word is used in a context that is incongruent with their expectations. However, infants in both groups did not show a difference between noun and verb test trials. Thus, no evidence for adaptation‐based learning was found. We propose that infants have to entertain strong expectations about syntactic contexts before they can adapt these expectations based on recent input. Abstract : We asked whether 18‐month‐old infants can use recent distributional information to categorize a novel word appearing in an ambiguous context. Both groups of infants failed to show evidence of having expectations about the novel word's syntactic category (verb vs noun).